The Voices of Students and Teachers Regarding the Integration of L1 in Online Grammar Classes - Aguskin, Lewinna Christiani; Maryani, Maryani (Celt: A Journal of Culture, English Language Teaching & Literature, 2024)
The integration of L1 in English classrooms has become a debatable issue due to its potential benefits and drawbacks. This research is conducted to investigate the perceptions of the university students and teachers regarding the use of L1 in online grammar classes during the pandemic. The purposes of integrating L1 in the teaching process and the impacts of integrating L1 on the students will be explored systematically. The participants of this study are 91 university students and four grammar teachers in a private university in Indonesia. The data is collected from the closed-ended questionnaire for the students and teachers as well as from the interviews with some students and teachers. Thus, descriptive and content analysis are used to analyze the data. The findings indicate that most students and teachers have positive perception regarding the integration of L1 to certain extent in online grammar classes. This study presents the insights on various impacts of integrating L1 on the students and various purposes intended by the teachers.